Killer game programming in Java - Davison, Andrew (O'Reilly Media, 2005)
Assuming a solid grounding in Java, this guide introduces the Java imaging and sound classes available in J2SE 1.4 and J2SE 5.0 for 2D games, and explains how to program 3D games using Java 3D, Java's scene graph API. Davison (computer engineering, Prince of Songkla University, Thailand) covers sampled audio synthesis, side scrollers, sprites, animation, particle systems, shooting techniques, landscape and scenery creation, and network programming. Annotation : 2005 Book News, Inc., Portland, OR (booknews.com).